2014
DOI: 10.1111/vde.12140
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ and CD8+ skin‐associated T lymphocytes in canine atopic dermatitis produce interleukin‐13, interleukin‐22 and interferon‐γ and contain a CD25+FoxP3+ subset

Abstract: Both CD4(+) and CD8(+) T cells are likely to contribute to the immunopathogenesis of cAD through the production of interleukin-13, interleukin-22 and interferon-γ. In both subsets, functional analysis of FoxP3(+) cells is essential to determine their role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 42 publications
2
30
0
Order By: Relevance
“…The results of these studies are sometimes difficult to compare because of methodological differences such as variation in antibodies, gating strategies and Treg definitions (CD4 + CD25 + , CD4 + FoxP3 + or CD4 + CD25 + FoxP3 + cells). Currently, Tregs in dogs are generally defined by the simultaneous expression of the markers CD4, CD25 and FoxP3 . In order to compare our results with those of previously published studies, we also analysed populations of CD4 + FoxP3 + cells.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The results of these studies are sometimes difficult to compare because of methodological differences such as variation in antibodies, gating strategies and Treg definitions (CD4 + CD25 + , CD4 + FoxP3 + or CD4 + CD25 + FoxP3 + cells). Currently, Tregs in dogs are generally defined by the simultaneous expression of the markers CD4, CD25 and FoxP3 . In order to compare our results with those of previously published studies, we also analysed populations of CD4 + FoxP3 + cells.…”
Section: Discussionmentioning
confidence: 91%
“…There was no difference in circulating Tregs of atopic and healthy dogs at baseline; an increase in the circulating Treg population of dogs with CAD during allergen‐specific immunotherapy was reported . The presence of CD4 + CD25 + FoxP3 + Tregs has recently been described in canine skin, although numbers were not significantly different between healthy and atopic dogs …”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have demonstrated an increase in the CD4/CD8 ratio and a decrease of CD8 + circulating T cells in the blood of atopic humans . A reduced ratio has also been reported in the lesional skin of atopic dogs . To the best of the authors' knowledge, no studies have been performed on blood of atopic dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the prolific number of studies which followed these initial experiments, together with more refined and reliable protocols in other species, canine skin organ culture models were never attempted. Cultured skin explants from dogs until now have been limited to either establishing keratinocyte cultures (Wilkinson et al, 1987) or to extract T-cells (Jassies-van der Lee et al, 2014). A single study in veterinary medicine reports on the histological similarities between human and swine skin and the establishment of Gottingen minipig skin organ cultures (Dame et al, 2008).…”
Section: Introductionmentioning
confidence: 99%